2023
DOI: 10.1186/s12889-023-15375-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in emergency department utilisation in Germany before and during different phases of the COVID-19 pandemic, using data from a national surveillance system up to June 2021

Abstract: Background During the COVID-19 pandemic and associated public health and social measures, decreasing patient numbers have been described in various healthcare settings in Germany, including emergency care. This could be explained by changes in disease burden, e.g. due to contact restrictions, but could also be a result of changes in utilisation behaviour of the population. To better understand those dynamics, we analysed routine data from emergency departments to quantify changes in consultatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The long-term impacts of cancer care delays and deferrals leading to more severe presentations are yet to be revealed [16,78]. Similar to other studies [26,27], we found that the rates of ED visits significantly declined at the start of the pandemic compared to the last prepandemic week, by 41% in Ontario and 24% in BC, and never returned to pre-pandemic levels in 2020. This is consistent with ED avoidance by people with milder conditions, diversion of human and diagnostic resources away from urgent care, as well as significant decreases in infections associated with lockdown measures.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The long-term impacts of cancer care delays and deferrals leading to more severe presentations are yet to be revealed [16,78]. Similar to other studies [26,27], we found that the rates of ED visits significantly declined at the start of the pandemic compared to the last prepandemic week, by 41% in Ontario and 24% in BC, and never returned to pre-pandemic levels in 2020. This is consistent with ED avoidance by people with milder conditions, diversion of human and diagnostic resources away from urgent care, as well as significant decreases in infections associated with lockdown measures.…”
Section: Discussionsupporting
confidence: 85%
“…The initial ramp-down started in March 2020 when Canadian healthcare systems began reducing elective procedures and non-emergency care [5,6,8], and reconfiguring facilities in preparation for COVID-19 patients [14,15]. In Canada and internationally, there were reports of major reductions in cancer screening [16][17][18][19], diagnosis [20], and treatment [21,22] in 2020 compared to previous years, as well as lower numbers of hospital admissions [23,24] and emergency department (ED) visits [10,11,[25][26][27]. While some non-COVID-19 care was transitioned from in-person to virtual [28][29][30][31][32] and from inpatient to outpatient [33], concerns about delivering ideal care under COVID-19 circumstances were identified [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, to estimate the effectiveness of population-level health interventions that have been implemented at a clearly defined point in time, Interrupted Time Series (ITS) regression analysis is the recommended method ( 15 ). However, the majority of research on this topic is monocentric ( 16–19 ), is restricted to specific pediatric age classes or considers all ages including adults ( 17 , 19–26 ), focuses on specific diagnoses ( 9 , 16 , 17 , 19 , 21 , 25 , 27 ), only looks at Emergency Department (ED) visits ( 16 , 17 , 19 , 21 , 23 , 26 , 28 , 29 ), or addresses the time period immediately following the pandemic onset without evaluating ongoing effects ( 18 , 25 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the use of pre-hospital EMS to the use of emergency departments during the early pandemic periods show some parallels: The most pronounced decreases occurred during the first and second wave [28]. Also, the decrease was stronger in young age groups [28,29] and in patients affected by trauma [6,30]. Other results were not on the same line: Studies looking at emergency department use report declines in patients with neurological symptoms [6,31,32] and cardiovascular disease [32].…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the use of pre-hospital EMS to the use of emergency departments during the early pandemic periods show some parallels: The most pronounced decreases occurred during the first and second wave [28]. Also, the decrease was stronger in young age groups [28,29] and in patients affected by trauma [6,30].…”
Section: Discussionmentioning
confidence: 99%